IMPLEMENTASI SUPERVISI AKADEMIK DALAM MENINGKATKAN KINERJA GURU DI SMA SJAKHYAKIRTI PALEMBANG - Sari, Putri Permata; Ahmad, Syarwani; Pahlawan, Pahlawan (STKIP Pesisir Selatan, 2025)
Academic supervision at Sjakhyakirti High School in Palembang, from planning to evaluation and follow-up, is carried out by an experienced supervisory team. This research aims to describe and analyze how the planning, implementation, evaluation, and follow-up of academic supervision are implemented to improve teacher performance. This research uses a descriptive qualitative approach with data collection methods including observation, interviews, and documentation. The research results show that the planning of academic supervision involves creating schedules and determining instruments that refer to the principal training module. The implementation of academic supervision includes scheduled observations in the classroom, completion of pre- and post-observation sheets by teachers as a form of